The degree of availability of social values among students of basic education stage A study on a sample of the fifth and sixth grade students in Lattakia - بوبو, منذر; حسون, هنادي; الحداد, نرمين (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
The study aimed to reveal the degree of availability of social values ​​among students of the basic education stage, and to identify the significance of differences in available social values ​​according to the two variables (gender, grade). The researcher used the descriptive and analytical method for its suitability to the research objectives. The study sample consisted of (106) students of the basic education stage, applying to them the social values ​​scale prepared by the researcher, which consisted of dimensions (cooperation, respect, friendship, bearing responsibility). The researcher verified its validity by presenting it to a group of arbitrators and its stability through the Cronbach alpha coefficient, which had a value of (0.81) and retested the value of the Pearson correlation coefficient (0.78), which is a high stability value. The study found a set of results indicating that there is no statistically significant difference between the mean scores of the study individuals on the scale of social values ​​according to the variables of gender and grade on the scale as a whole and on the following scale dimensions (cooperation, respect, friendship, bearing responsibility). Where the differences were just honesty. The study recommended conducting comparative studies in the social values ​​of other groups in society, and focusing on activities that develop social values ​​among studentse.